(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: In today’s modern era, a visible gap in emotional, communication, role expectation and family support has emerged between children and parents, primarily due to quick advancements in artificial intelligence and other new technology. Numerous psychological challenges just like loneliness, isolation, identity crisis faced by our elderly people experience have been caused by the technology gap. The aim of our study is to bring these concerns to the forefront, address them effectively and provide practical solution through understanding of these factors of psychosocial correlates that influence the family relationship, self-concept and life satisfaction of elder adults. Method: In current research correlational research design were selected and data were collected from the sample of 155 Males and 129 Females along with demographic Performa for assessment Brief Family Relationship (Fok et al., 2014) Self Concept Clarity (Jennifer D. Campbell et al., 1996) and Life Satisfaction Index for the Third Age (Peter, S. D., & Andrew, F.,2009) were used. To evaluate data psychometric properties, pearson product moment correlation, mediation (SEM PLS) and t test was done. Results: The findings revealed that elder individuals have high level of satisfaction with their lives with good family relations. Among them the idea of good relation with family was the most important determinant of psychosocial correlates for self-concept and life satisfaction of individuals with golden age. Moreover, in later life, self-concept becomes more defined, and life satisfaction increases with strong familial relationships. Conclusion: Research findings will be helpful for people who are not living with their families not giving time because of AI and new gadgets takes up much of their time which has resulted in a growing generational gap.